Doxazosin Treatment Alters Stromal Cell Behavior and Increases Elastic System Fibers Deposition in Rat Prostate - Delella, Flávia Karina [UNESP]; Felisbino, Sergio Luis [UNESP] (Wiley-liss, 2010)
Doxazosin (DOX), an alpha-adrenoceptor antagonist, induces the relaxation of smooth muscle cell tonus and reduces the clinical symptoms of benign prostatic hyperplasia (BPH). However, the effects of DOX in the prostate stromal microenvironment are not fully known. In a previous study, we showed that DOX treatment for 30 days increased deposition of collagen fibers in the three rat prostatic lobes. Herein, we investigated the effects of DOX on stromal cell ultrastructure and elastic fiber deposition. Adult Wistar rats were treated with DOX (25 mg/kg/day); and the ventral, dorsal, and anterior prostates were excised at 30 days of treatment. The prostatic lobes were submitted to histochemical and stereological-morphometric analyze and transmission electron microscopy (TEM). Histochemical staining plus stereological analysis of the elastic fiber system showed that DOX-treated prostatic lobes presented more elaunin and elastic fibers than controls, mainly in the ventral lobe. Ultrastructural analysis showed that fibroblasts and smooth muscle cells from DOX-treated prostates presented active synthetic phenotypes, evidenced by enlarged rough endoplasmic reticulum and Golgi apparatus cisterns, and confirmed the observation of thickened elaunin fibers. Our findings suggest that, under alpha-adrenergic blockade by DOX, the fibroblasts become more active and smooth muscle cells shift from a predominantly contractile to a more synthetic phenotype. The deposition of collagen and elastic system fibers in the prostatic stroma may counterbalance the absence of smooth muscle tone during alpha-blockers treatment. Microsc. Res. Tech. 73: 1036-1044, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: doxazosin; prostate; extracellular matrix; elastin; smooth muscle cell